A longitudinal study of the impact of change in socioeconomic status on dental caries in the permanent dentition of Swedish children and adolescents. Issue 4 (26th April 2020) - Östberg, Anna‐Lena; Petzold, Max
Abstract: Objectives: The overall aim was to analyse longitudinally the development of dental caries in the permanent dentition of children and adolescents in a Swedish region, in relation to possible change in socioeconomic status (SES). Methods: A total of 259 448 individuals in western Sweden were followed over a 3‐year period, through dental journal records at baseline (3‐19‐year‐olds) and 1‐3 dental check‐ups during the follow‐up period. Official socioeconomic register information (ethnicity, wealth, parental education and employment) was available at both baseline and follow‐up. Data were used both as independent single variables and combined in an index. Gender, age and caries status at baseline and the examination years were included as covariates in the regression models. Results: Associations over time were found between SES and dental caries in young people. A persistently low SES was associated with the greatest risk of both new and accumulated (decayed plus filled teeth/approximal surfaces) caries; however, any change in SES, whether improved or worsened, led to a greater risk. An increased risk of new caries events was identified for those who were older at baseline and by examination year. On average, the increase per year in decayed and/or filled teeth and in approximal surfaces was 0.23 and 0.12, respectively. Conclusion: SES was shown to be an important risk factor for dental caries over time in young Swedish people. Prevention programmes should pay particular attention to the needs of socioeconomically vulnerable individuals and groups.